Alaska Commercial Co. steamboat HANNAH tied to a landing on the Yukon River, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "A.C. Co. str. Hannah. Yukon River" Original image in Hegg Album 17, page 39.